An assessment of mediolateral knee and ankle acceleration as an indicator of fatigue - Fischer, E.; McDonough, E.; Dodd, K.; Thiel, D. V. (Journal of Fitness Research, 2016)
Lower limb injuries in football (soccer) are caused by a lack of muscle strength and fatigue. The mediolateral acceleration of the knee and ankle was measured during a simple running exercise using 25 elite football players over a full playing season (26 weeks). Each run was compared using acceleration skewness comparing base line and fatigue. Most (79%) participants exhibited significant changes (0.002 < p < 0.044) in left-ankle acceleration skew, and 55% (0.0003 < p < 0.045) in right-ankle acceleration skew. Recording ankle and knee accelerometer data and analysing for skewness offers a potential detection method for fatigue assessment